2015
DOI: 10.1002/jat.3266
|View full text |Cite
|
Sign up to set email alerts
|

The minipig as a new model for the evaluation of doxorubicin‐induced chronic toxicity

Abstract: Doxorubicin can cause life-threatening toxic effects in several organs, with cardiotoxicity being the major concern. Although a large number of animal models have been utilized to study doxorubicin toxicity, several restrictions limit their use. Since the Göttingen minipig is an accepted species for non-clinical safety assessment and translation to man, we aimed at exploring its use as a non-rodent animal model for safety assessment and regulatory toxicity studies using doxorubicin. Three groups of three males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
4
11
0
Order By: Relevance
“…A similar trend was seen for females of CC 019 and CC 042. Consistent with previously reported data across animal species (Bertinchant et al 2003; Desai et al 2013; Manno et al 2016), doxororubicin -treated animals demonstrated impaired growth over time compared to age matched vehicle treated controls. This varied by strain and sex.…”
Section: Resultssupporting
confidence: 90%
“…A similar trend was seen for females of CC 019 and CC 042. Consistent with previously reported data across animal species (Bertinchant et al 2003; Desai et al 2013; Manno et al 2016), doxororubicin -treated animals demonstrated impaired growth over time compared to age matched vehicle treated controls. This varied by strain and sex.…”
Section: Resultssupporting
confidence: 90%
“…The changes in the blood cells especially erythrocytes, platelets, and leucocyte count were all DOX dose dependent and were consistent with the findings reported by Manno et al [ 5 ]; Tacar et al [ 51 ], which could be attributed to the known bone marrow suppressive effect of DOX and iron-DOX interaction, thus causing RBC membrane rupture as previously reported by Vici et al [ 52 ] and Pahouja et al [ 53 ] since DOX did not limit its effects not only to cancer cell alone but also to proliferating haematopoietic cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, the carrier molecules are entrapped within the slit diaphragm due to the size of the carrier molecules used in drug delivery leading to renal tubular tissue injury [ 82 ]. The glomerular and tubular damage observed in our study was similar to the lesion seen in rodent as reported by Cianciolo et al [ 83 ] and Manno et al [ 5 ] in rodent and mini pig animal models, respectively. In addition, our results also agree with the works of Anan et al [ 84 ] as clusters of nuclear material were observed as a result of free radical production from lipid peroxidation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To augment studies in mice, new animal models of cancer are needed. The pig is a promising alternative model organism due to its high degree of similarity to humans, including longevity, size, organ anatomy, physiology, drug metabolism, genetics, and immunology (Flisikowska et al, 2013;Forster et al, 2010;Kuzmuk and Schook, 2011;Manno et al, 2016;Mote and Rothschild, 2006;Wernersson et al, 2005). Importantly, the large size of pigs also brings opportunities for longitudinal sampling and therefore monitoring of tumor evolution during treatment, which is generally not possible in rodents.…”
Section: Introductionmentioning
confidence: 99%